Triglyceride Form of Docosahexaenoic Acid Mediates Neuroprotection in Experimental Parkinsonism - Gómez-Soler, Maricel; Cordobilla, Begoña; Morató, Xavier; Fernández-Dueñas, Víctor; Domingo, Joan C.; Ciruela, Francisco (Frontiers in Neuroscience, 2018)
Parkinson’s disease (PD) is a neurodegenerative disorder of unknown etiology. The main treatment of PD consists of medication with dopamine-based drugs, which palliate the symptoms but may produce adverse effects after chronic administration. Accordingly, there is a need to develop novel neuroprotective therapies. Several studies suggest that omega-3 polyunsaturated fatty acids (n-3 PUFA) might provide protection against brain damage. Here, we studied several experimental models of PD, using striatal neuronal cultures, striatal slices, and mice, to assess the neuroprotective effects of docosahexaenoic acid (DHA), the main n-3 PUFA in the brain, administered in its triglyceride form (TG-DHA). Hence, we determined the beneficial effects of TG-DHA on neural viability following 6-hydroxydopamine (6-OHDA)-induced neurotoxicity, a well-established PD model. We also implemented a novel mouse behavioral test, the beam walking test, to finely assess mouse motor skills following dopaminergic denervation. This test showed potential as a useful behavioral tool to assess novel PD treatments. Our results indicated that TG-DHA-mediated neuroprotection was independent of the net incorporation of PUFA into the striatum, thus suggesting a tight control of brain lipid homeostasis both in normal and pathological conditions.